Physical and Functional Properties of Spent Coffee Ground after Various Drying Techniques - Nur Maiyah; Yatima Auenchitr; Suriyan Supapvanich; Arpassorn Sirijariyawat; Pajaree Ingkasupart; Natthaporn Chotigavin; Soraya Kerdpiboon (Key engineering materials, 2025)
Spent coffee ground (SCG) consists of impact compositions and functional ingredients that could be applied to food products. Drying techniques and conditions had an impact on the qualities of SCG. The aim of this research was to investigate the chemical compositions of roasted coffee ground (CG) and SCG from Arabica (A) and Robusta (R) coffee, as well as the physical and functional properties of SCG before and after different drying using hot air tray dryer and freeze dryer. It was found that SCG had moisture and carbohydrate content of 64.79–65.87% wb and 16.55–18.57%. Arabica spent coffee ground (ASCG) had more lipid and less protein, caffeine and phenolic content than that of Robusta spent coffee ground (RSCG). The dried SCG had moisture content lower than 5% for all drying conditions. Moreover, the dried SCG had Aw, solubility, and rehydration in a range of 0.25-0.55, 6.02-6.92%, and 140.67-180.37%, respectively. Freeze-dried SCG retained more functional ingredients than tray-dried SCG across all drying conditions.
Keywords: Coffee research and impacts; Urban Agriculture and Sustainability